Препарати альфа-ліпоєвої кислоти у комплексному лікуванні діабетичної нейропатії у підлітків - Большова, О. В. (Clinical Endocrinology and Endocrine Surgery, 2011)
It is shown that the preperation of alpha-lipoic (thioctic) acid Berlition is sufficiently effective and safe in treatment of diabetic neuropathy.Its use contributes to significant improvement in general condition, normalization of autonomic regulation, effectively reduces the manifestations of pain, leading to the restoration of all kinds of sensitivity and is effective in prevention of diabetic foot. Does not cause side effects. The article concludes that given the high probability of damage to the nervous system early after manifestation of diabetes drugs are alphaipoic acid, it is expedient to appoint is already at the preclinical stage of neuropathy.Neurological examination should be mandatory, especially when the duration of diabetes over 3 years and in children of pubertal age.